1984
DOI: 10.1172/jci111622
|View full text |Cite
|
Sign up to set email alerts
|

Volume-independent reductions in glomerular filtration rate in acute chloride-depletion alkalosis in the rat. Evidence for mediation by tubuloglomerular feedback.

Abstract: Abstract. We have recently described reduced superficial nephron glomerular filtration rate (SNGFR) in chloride-depletion alkalosis (CDA) without volume depletion. To elucidate the mechanism of this phenomenon, we studied three degrees of increasing severity of CDA (groups CDA-1, 2, and 3) produced by one or two peritoneal dialyzes against 0.15 M NaHCO3 and electrolyte infusions of different Cl and HCO3 content in Sprague-Dawley rats; control rats (CON) were dialyzed against and infused with Ringers-HCO3. Extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The mechanisms by which lower chloride leads to an increased risk of adverse events, however, remains unclear. Lower serum chloride levels may represent several downstream effects of maladaptive mechanisms in heart failure: increased arginine vasopressin release, the pleotropic effects of excess angiotensin II on renal sodium and water handling, and altered acid–base homeostasis …”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which lower chloride leads to an increased risk of adverse events, however, remains unclear. Lower serum chloride levels may represent several downstream effects of maladaptive mechanisms in heart failure: increased arginine vasopressin release, the pleotropic effects of excess angiotensin II on renal sodium and water handling, and altered acid–base homeostasis …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Na depletion, however, Cl depletion may be a more specific electrolyte marker for impaired diuretic response because this association was independent of both Na, bicarbonate, and cystatin C. Murine models have suggested that systemic Cl depletion is essential for mediating a contraction alkalosis and can effect tubuloglomerular feedback, independent of volume expansion. 19,20 As a result, Cl depletion may lead to diuretic resistance by fueling adaptive renal mechanisms to maintain volume status.…”
Section: Discussionmentioning
confidence: 99%
“…As Cl depletion evolves, lower levels of Cl signal a reduction in glomerular filtration rate, which is the normal homeostatic response to lower delivery of bicarbonate to the distal nephron, thus attenuating further Na and fluid losses. 20 Therefore, changing renal function during decongestive therapies may be mediated, at least in part, by Cl imbalance underscoring the complex interplay between hemodynamic and non-hemodynamic determinants of renal function during AHF. 21 …”
Section: Discussionmentioning
confidence: 99%
“…First, GFR was inversely correlated with the degree of CDA by tubuloglomerular feedback. 12 Although intact function of the proximal tubule and the loop of Henle are essential to the renal response, these segments have no identifiable adaptive role in the corrective response to chloride repletion in that glomerulotubular balance is maintained whether CDA is being corrected. 8,9 Delivery of chloride and bicarbonate out of the loop of Henle was not different whether rats were maintaining or correcting CDA.…”
mentioning
confidence: 99%